2000
DOI: 10.1089/15246090050147754
|View full text |Cite
|
Sign up to set email alerts
|

Improving Follow-Up after an Abnormal Pap Smear: Results from a Quasi-Experimental Intervention Study

Abstract: The success of cervical cancer control programs depends on regular screening with the Pap smear test and prompt and appropriate treatment of early neoplastic lesions. Recognizing the potentially grave consequences of lack of follow-up for abnormal Pap smears, numerous intervention studies have tested the impact of a variety of strategies to increase return for follow-up. The majority of these studies were evaluated under controlled experimental conditions. Despite the encouraging findings of these trials, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…Although screening rates for cervical cancer remain high, 19 appropriate diagnostic evaluation of abnormal screening tests and therapeutic intervention for pre-invasive neoplasia is necessary to reduce cervical cancer incidence and mortality. Our study suggests that compared to historical controls, [11][12][13] lost to follow-up rates have declined in this county healthcare system. However, for those that did return for follow-up care, a substantial proportion of women are receiving less than optimal follow-up care as defined by practice guidelines.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Although screening rates for cervical cancer remain high, 19 appropriate diagnostic evaluation of abnormal screening tests and therapeutic intervention for pre-invasive neoplasia is necessary to reduce cervical cancer incidence and mortality. Our study suggests that compared to historical controls, [11][12][13] lost to follow-up rates have declined in this county healthcare system. However, for those that did return for follow-up care, a substantial proportion of women are receiving less than optimal follow-up care as defined by practice guidelines.…”
Section: Discussionmentioning
confidence: 74%
“…10 Other studies have shown that lost to follow-up rates in women seen at inner-city, public healthcare facilities vary from 20 to 50%. [11][12][13][14][15] Several interventional studies have been performed in the LACHS directed at reducing lost to follow-up rates; however, they did not address the quality of care that women received. [11][12][13] Of approximately 50 million women undergoing Pap testing each year, 3.5 million (7%) of the women will require additional follow-up and evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on prior work in these settings (20)(21)(22)(23)(24)(25) and on the judgments and preferences of county clinicians and administrators, the major aim of the study was to improve diagnostic resolution (malignant or benign) versus to increase attendance at first diagnostic appointment. This was based on the observation that despite a fairly high rate of attendance at first diagnostic appointment (e.g., 84% in this study in treatment and control groups, and both hospitals as indicated in Table 1), the rate of diagnostic resolution was unacceptably low (56% in this study, as indicated in Table 1).…”
Section: Objective and Hypothesismentioning
confidence: 99%
“…[1][2][3] Women from groups of racial/ethnic minorities and low education and income have limited access to healthcare and are less likely to seek care after an abnormal result. [4][5][6][7][8] In 1990, Freeman introduced the model of patient navigation as a way to support screening for, timely diagnosis of, and then treatment of cancer among vulnerable women.…”
mentioning
confidence: 99%